September 2019 PovcalNet Update : What's New - Atamanov, Aziz; Castaneda Aguilar, R. Andres; Diaz-Bonilla, Carolina; Jolliffe, Dean; Lakner, Christoph; Mahler, Daniel Gerszon; Montes, Jose; Moreno Herrera, Laura Liliana; Newhouse, David; Nguyen, Minh C.; Prydz, Espen Beer; Sangraula, Prem; et al. (World Bank, Washington, DC, 2019)
The September 2019 global poverty update from the World Bank includes revised survey data which lead to minor changes in the most recent global poverty estimates. The update includes revisions to 18 surveys from four countries. As a result of the revised data, the estimate of the global 1.90 US Dollars headcount ratio for 2015 increases slightly from 9.94 percent to 9.98 percent, whereas the number of poor increases from 731.0 million to 734.5 million people.